Outside-in Politicization of EU–Western Africa Relations: What Role for Civil Society Organizations? - Friedrich Plank; Niels Keijzer; Arne Niemann (JCMS: Journal of Common Market Studies, 2021)
This article explores the empirical relevance of researching outside-in politicization processes in European studies. To this end, it examines to what extent and how civil society organizations (CSOs) have contributed to the politicization of EU policies towards Western Africa in two cases: the negotiation of Economic Partnership Agreements and the EU's engagement with the G5 Sahel. CSOs were strongly engaged in the trade negotiations, while they were largely excluded from the G5 Sahel process. In both cases this was due to CSOs' own initiatives, or the absence thereof, with these strongly linked to being either invited or discouraged by official actors. The article argues that authority transfer and the domestic context – including state fragility and state–society relations – are relevant to explaining the (non-)involvement of CSOs in outside-in politicization.
Keywords: 330; politicization; outside-in politicization; Western Africa; civil society organizations; European Union